The Spatiality of the Social Media Crowd in Okky Madasari’s Kerumunan Terakhir - Sri Kusumo Habsari (Asiatic: IIUM Journal of English Language and Literature, 2022)
Okky Madasari’s Kerumunan Terakhir (2016) explores the complicated interaction between its male protagonist and the disruptive context of modern Indonesia following the triumph of communication technology. Her narrative illustrates the influences of feminine authority as embodied by the characters of the grandmother, mother, and girlfriend to the development of the protagonist’s subjectivity to adapt to the dynamics of space between tradition and modernity. Drawing loosely from three theoretical apparatuses by Lefebvre, Foucault, and Soja, this article attempts to explain the embodiment of spatial conflicts and the individual aspiration of future uncertainties. In his refusal to accept the unexpected trialectics of home, the protagonist seeks refuge by embracing the virtual world’s fluidity and lack of boundaries. Haunted by the influence of the three important women in his life and frustrated by his inability to define himself, he adjusts to living in the ambivalence of social media crowds, which offers him heterotopia and creates a thirdspace. This article discusses Okky Madasari’s pessimistic voice to individual vulnerability to the loudness of the virtual world, which created a disruptive space.